SOME INSIGHTS ON WHY ROMANIA SHOULD BE DOWNGRADED TO JUNK STATUS IN 2025 - Adrian NEGREA; Adriana GIURGIU; Ciprian Beniamin BENEA (Oradea Journal of Business and Economics)
In 2025, Romania’s potential downgrade to junk status could be driven by a combination of worsening fiscal health, political instability, economic slowdown, and external challenges. A downgrade would likely reflect a loss of confidence in the country’s ability to maintain economic stability, service its debt, and attract investment. However, such a scenario would likely be preceded by warning signals, such as increased debt levels, budget deficits, economic contraction, or growing political unrest. Downgrading a country’s credit rating to «junk» status is a serious financial move and would typically be based on a range of economic, fiscal, and political factors. If Romania were to face such a downgrade in 2025, the reasons could stem from several issues. Rising government debt level, which is today almost 54% of the GDP, it could become a concern for investors, especially if the country struggles to meet its debt obligations or service the debt. The 7% annual budget deficit negotiated with the European Commission could be in peril and if it increases, it could create uncertainty around the ability to manage public finances effectively. The fail to enact sufficient reforms to stabilize Romania’s finances combined with a lack of political will to implement harsh fiscal consolidation measures could lead to a downgrade. If the economy slows down significantly or enters a recession, it could raise doubts about the country’s future economic prospects, and the USA tariffs are a big push in that direction, hitting the country traditional European trade partners, due to the fact that more than 70% of goods and services are traded with the EU. Due to these factors, the paper addresses the possibility of a downgrade to JUNK status for the Romanian economy, and what the economic impact should be, plus the necessary measures that have to be addressed in order to put the economy back on track. The paper will analyze statistical data from Eurostat, UNCTAD statistical data base, and TradingEconomics in order to assess the impact and possible measures in comparison the what Greece and Argentina did in order to improve their countries rating. Romania doesn’t have to invent the weal; it can learn from other countries best case scenarios and the good case measures that those economies have taken. Despite some credit agencies downgrade, the Romanian economy has the potential to recover quickly, supported by strong domestic measures, resilient growth sectors, and a proactive governmental approach to economic stability.